Morphology of Neoheegeria dalmatica Schmutz, 1909 (Thysanoptera, Phlaeothripidae) larvae—their diagnostic characteristics - Kucharczyk, Halina; Kucharczyk, Marek; Saj, Izabella (Zootaxa, 2024)
This paper presents morphological description and images of the larval instars of Neoheegeria dalmatica as well as observations on its life cycle and relationships with host plants in a temperate climate. It also compares characteristics of the second larval instar with those of Haplothrips verbasci, i.e. a species previously placed in the genus Neoheegeria. The main characteristic that differentiates the larvae of both species is, among others, the sculpture of their cuticle, which is smooth in H. verbasci and covered by dense microtrichia in N. dalmatica.